2009
DOI: 10.1001/archgenpsychiatry.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Role of GABRA2 in Trajectories of Externalizing Behavior Across Development and Evidence of Moderation by Parental Monitoring

Abstract: Context As we identify genes involved in psychiatric disorders, the next step will be to study how the risk associated with susceptibility genes manifests across development and in conjunction with the environment. We describe analyses aimed at characterizing the pathway of risk associated with GABRA2, a gene previously associated with adult alcohol dependence, in a community sample of children followed longitudinally from childhood through young adulthood. Objective To test for an association between GABRA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
150
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 78 publications
17
150
1
Order By: Relevance
“…The G allele of GABRA2 SNP rs279858 has been associated with adult alcohol dependence (Covault et al, 2004), elevated externalizing problems throughout adolescence (Dick et al, 2009), impulsiveness (Villafuerte et al, 2012), and increased insula activation during incentive anticipation (Villafuerte et al, 2012). We show that activation of the NAcc to incentive stimuli is heightened in G carriers during adolescence.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The G allele of GABRA2 SNP rs279858 has been associated with adult alcohol dependence (Covault et al, 2004), elevated externalizing problems throughout adolescence (Dick et al, 2009), impulsiveness (Villafuerte et al, 2012), and increased insula activation during incentive anticipation (Villafuerte et al, 2012). We show that activation of the NAcc to incentive stimuli is heightened in G carriers during adolescence.…”
Section: Discussionmentioning
confidence: 66%
“…The less frequent haplotype has been associated with alcoholics without comorbid drug dependence (Covault et al, 2004) and those with a family history of alcoholism (Fehr et al, 2006). This haplotype is also associated with childhood and adolescent phenotypic precursors to alcohol dependence, including externalizing problems throughout adolescence (Dick et al, 2009) and impulsiveness (Villafuerte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive neuroscience methodologies, especially, offer powerful tools to examine the phenotypic expression of genotypic variation in brain activity (e.g., Edenberg et al, 2004;Filbey et al, 2008;McClernon, Hutchison, Rose, and Kozink, 2007; for a review, see Green et al, 2008). However, there is also promise for many of the other experimental domains reviewed, such as subjective intoxication (e.g., Dlugos et al, 2010;Ray and Hutchison, 2004), cue reactivity (Hutchison et al, 2002;van den Wildenberg et al, 2007), aspects of impulsivity (e.g., Eisenberg et al, 2007;Hamidovic et al, 2009), and even developmental trajectories (e.g., Dick et al, 2009). Although it is highly likely that each of these phenotypes in themselves will be complex, with variation reflecting the influences of tens, hundreds, or even thousands of loci, they may nonetheless be important mechanistic processes that add to our understanding of latent vulnerabilities to addiction.…”
mentioning
confidence: 99%
“…A limited number of studies have examined the specific sources of parental monitoring as they relate to child behavioral outcomes (Dishion, et al, 1991;Dick et al, 2009& Fulkerson, Pasch, Perry, & Komro, 2008. In the literature on the relationship between monitoring and child outcomes, only three studies were identified that utilized the specific sources of parental monitoring (Crouter, et.…”
Section: Problem Behaviorsmentioning
confidence: 99%